Pengaruh Pendapatan Tenaga Kerja Indoenesia dan Lingkungan Sosial Terhadap Perilaku Konsumsi di Ponorogo Menurut Perspektif Ekonomi Islam. - Desi Fitriana; Hanik Fitriani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to determine the effect of income and social environment on consumption behavior in Ponorogo according to the Islamic Economic Perspective. This research uses quantitative methods. The sample used was 97 respondents who became migrant workers and worked abroad. This sampling technique uses purposive sampling technique hypothesis testing using multiple linear analysis and classical assumption test using the SPSS version 25 application. Based on the results of the analysis conducted, that the variable income of migrant workers, and the social environment has a positive and significant effect on family consumption behavior in Ponorogo both partially and simultaneously.